Teaching ethics through literature : the significance of ethical criticism in a global age - Choo, Suzanne S. (Abingdon, Oxon, New York : Routledge, 2021)
"Teaching Ethics through Literature provides in-depth understanding of a new and exciting shift in the fields of English education, Literature, Language Arts, and Literacy through exploring their connections with ethics. The book pioneers an approach to integrating ethics in the teaching of Literature. This has become increasingly relevant and necessary in our globally connected age. A key feature of the book is its integration of theory and practice. It begins with a historical survey of the emergence of the ethical turn in Literature education and grounds this on the ideas of influential Ethical Philosophers and Literature scholars. Most importantly, it provides insights into how teachers can engage students in ethical concerns through rich on-the-ground case studies of high school Literature teachers in Australia, Singapore and the United States"--
Includes bibliographical references and index.
Keywords: Moral education; Ethics -- Study and teaching; Literature -- Study and teaching; Ethics in literature